A Galiza (não) é longe daqui--: lendo(-se) em imagens, mirando(-se) em textos - Vidal Bouzon, Álvaro J. (2007)
Through the analysis of artistic and written artifacts, this dissertation attempts to reflect upon the cultural and political conditions that conjoin to constitute a highly unstable "Galizan identity". The dissertation will begin by reading how a graphic work by the single most central figure in modern Galizan nationalism managed to convey such unstable identity. It will then go on to assess how culture in general, and literary production in particular might be used to mobilize the social elements that would liberate a potential Galizan identity/nation, according to the terms of a contemporary Galizan manifesto-cum-declaration and under the conditions which have historically produced the cultural, social and political map of the Iberian Peninsula. The special situation of Galiza comes across, thus, as perhaps the most complex identitarian conflict of those locked up by the Spanish Kingdom. Amongst all the potential indicators of a "Galizan identity", language retains a hegemonic position (of which the artifacts under study here are perfect paradigms) at the same time that it has become the privileged territory for the confrontation of different national projects. The combination of this cultural constituent factor with other historic elements allows for the categorization of Galiza as an enclave in an unequal dialectical relationship. This characterization depends, however, upon the privileged status given to the Nation-State in Modernity as the site of political sovereignty. Assuming as much, the artifacts analysed in this dissertation can only present Galiza as being either a nation's "amputated/occupied segment" or a "forbidden" nation (without "its own Nation-State"). Nevertheless, in the Global Era, the "suspended" condition of Galizan identity may become one of the aporetic paradigms of subjectivity at the beginning of the new century: Galizans can and cannot be (an)other thing. Their incompleteness is, thus, not only the very condition of their foreignness to the two Nation-States of the Iberian Peninsula but, above all, to the modern political construct that the Nation-State is.